Ocular movement abnormalities and ptosis after glaucoma surgery: A retrospective decade long analysis - Carlo Catti; Federica Tessitore; Daniele Ferrari; Federica Milanesi; Silvia Acerra; Luigi Peci; Arianna Rizzi; Silvio Semeria; Irene Schiavetti; Carlo Alberto Cutolo; Michele Iester; Aldo Vagge (PLoS ONE, 2025)
Background/Aims To evaluate the prevalence of ptosis, strabismus and the combination of both after glaucoma surgery and determine which kind of surgery is most likely to be linked to these complications. Methods A total of 705 clinical records of patients who underwent glaucoma surgery at the University Eye Clinic of IRCCS Ospedale Policlinico San Martino, Genoa, from January 1, 2010, to December 31, 2020, were retrospectively evaluated. Surgery procedures were divided in three groups: “Ab interno”, “Ab externo” and “Muscle isolation”. Results Out of all patients 26 developed ptosis alone (3.7%), two developed bilateral ptosis, with a mean of 2.2 ± 1.08 procedures per patient. Highest incidence of ptosis was noticed in patients who underwent muscle isolation surgery (5.7%). Twelve patients developed strabismus alone (1,7%), four underwent unilateral surgery and eight bilateral surgery, with an average of 3.3 ± 1.78 procedures per patient. Strabismus was more frequent following extraocular muscle manipulation surgery (7.5%), showing a statistically significant difference (OR: 6.57; 95% CI: 1.71–21.65; p = 0.003) Seven patients developed both strabismus and ptosis (1.0%), one patient with bilateral ptosis. Four underwent bilateral surgery and three underwent unilateral surgery. The mean number of surgeries was 2.9 ± 1.07, showing a statistically significant difference compared to the uncomplicated glaucoma group (OR: 1.58; 95% CI: 1.01–2.25; p = 0.02). The prevalence of both ptosis and strabismus was higher after muscle isolation surgery (1.9%). Conclusion Ptosis, strabismus and the combination of both are rare complications after glaucoma surgery, mostly linked to surgery with muscle isolation.